anonymous
  • anonymous
x^4+x^2-6=0
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
RadEn
  • RadEn
directly factor out it, becomes x^4+x^2-6=0 (x^2 + 3)(x^2 - 2) = 0 set each factor be equal zero then solve for x
anonymous
  • anonymous
thanks i really dont remember how to do it
RadEn
  • RadEn
first, take x^2 + 3 = 0 this cant be factored, so use the quadratic formula : x = (-b +- sqrt(b^2 - 4ac))/(2a) here, known a = 1, b = 0 and c = 3

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
thanks
RadEn
  • RadEn
for the 2nd case, to solve of equation : x^2 - 2 = 0, it can be factored (x + sqrt(2)) (x - sqrt(2)) = 0 set all factor equal zero, then solve for x. x + sqrt(2) = 0 x = - sqrt(2) (x - sqrt(2) = 0 x = sqrt(2) if the domain of x is real nmber, so the solution for x = { - sqrt(2), sqrt(2)}
anonymous
  • anonymous
so there are 4 answers
RadEn
  • RadEn
yeah, if the imaginer number allow here
anonymous
  • anonymous
is this the equation for the first one -0+-√0^2-4(1)(3)/2(1)
RadEn
  • RadEn
yes, just simplify again then
anonymous
  • anonymous
would it end up being √-4(1)(3)/2
anonymous
  • anonymous
because u cant square root 0
RadEn
  • RadEn
yup, or it can simplied becomes +- √-4(1)(3)/2 = +- (√-12)/2 = +- (√4 * 3 * -1)/2 = +- (√4 * √3 * √-1)/2 = +- 2(√-3)i/2 = +- 2i√3 (dont forget about the sign of +- infront of the square root, and we knowed that i = sqrt(-1))
anonymous
  • anonymous
can i also ask u another question
bradely
  • bradely
step by step answer http://www.mathskey.com/question2answer/

Looking for something else?

Not the answer you are looking for? Search for more explanations.